In vitro Mass Propagation of Artemisia (Artemisia annua L.) cv: Anamed - Hailu, Tilahun; Abera, Balcha; Mariam, Gabra (Plant Tissue Culture and Biotechnology, 2014)
An efficient in vitro propagation protocol was developed for anamed (A-3) cultivar of Artemisia annua. Two and 1.5% concentration of NaOCl treatment for 10 and 20 min were found to be optimum for sterilization of shoot tip and nodal explants, respectively. Maximum percentage (98.75 ± 2.50) shoot induction was observed from nodal explants cultured on MS supplemented with 0.8 mg/l BAP + 0.1 mg/l IBA followed by 82.50 ± 2.88% from shoot tip explants on the same medium with 0.8 mg/l TDZ for shoot tip explants. The highest number of shoots (8.05 ± 0.66/explant) was regenerated on MS + 1 mg/l BAP + 0.1 mg/l IBA. Best rooting with mean values of 18.25 ± 0.95/explant root number and root length (6.35 ± 0.10 cm) was recorded on 1/2 MS + 0.5 mg/l IBA. Up on acclimation and transplanting, 80% survival efficiency was observed on the soil mix ratio of 2 : 1 : 1 (decomposed coffee husk, forest soil and sand, respectively). The developed regeneration protocol enables a large scale commercial production and a possible system towards the genetic improvement of this crop. D. O. I. http://dx.doi.org/10.3329/ptcb.v23i2.17518 Plant Tissue Cult. & Biotech. 23(2): 165-176, 2013 (December)